Sistem Pendukung Keputusan untuk Seleksi Penerima Beasiswa BBP-PPA dengan Metode TOPSIS berbasis Web - Nova Noor Kamala Sari; Widiatry Widiatry; Nadya Chitayae (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The scholarship is a development program obtained by the students to be able to enroll their studies, in the form of financial assistance. At the Economics Institute of Palangka Raya, there is a BBP-PPA Scholarship to help the students who are financially disadvantaged. In selecting the scholarship awardees, Economics Institute of Palangka Raya experienced difficulties due to a large number of prospective scholarship awardees. Because of that, the Economics Institute of Palangka Raya disposes to accelerate the selection process by using one criterion, that is by grading the students’ GPA. This process might be inaccurate, indeed the selection process will be much quicker by that GPA rank criterion. Yet it is inappropriate considering other several criteria that have to be considered carefully as well. Thus, the solution to this problem is to establish the Decision Support System to select the BBP-PPA scholarship awardees which are web-based. The Decision Support System (DSS) uses the Technique for Order Preference Method by Similarity to Ideal Solution (TOPSIS). In developing the DSS, it will apply Waterfall software development methodology as Ian Sommerville’s. The software used in building this website is Notepad ++, SQLyog, and XAMPP. This system can run well as black box testing on the system.